Dyeing Cotton Fabric with Direct Dyes Using Electrochemical Processes - Kalapriya K. (Chemical and Materials Sciences - Developments and Innovations Vol. 1, 2024)
The electrochemical method of dyeing can be an alternative way of minimizing the consumption of chemicals. Electrochemical reduction of indigo, Sulphur and vat dyes can be considered as an alternative way for environmental and productive reasons. Electrochemical reduction can be carried out by direct and indirect methods. An attempt has been made with two-fold aims: (I) dyeing of cotton fabric by the application of electrical potential (2V, 3V, 4V) (II) to improve the dyeability by embedding the textile substrate on the electrode. The electrochemical dyeing process offers a reduction in the usage of additives compared to traditional methods. Additionally, the application of an external electric field enhances the availability of chemical sites for dyes in the dyeing solution while reducing them in the fibers. The novelty is an environmentally friendly method of dyeing with less consumption of energy.